Myxedema Ascites: An Unusual Presentation of Uncontrolled Hypothyroidism - Dhingra, Rohit (Cureus, 2018)
We describe a case of myxedema ascites in a 64-year-old male with a history of hypothyroidism noncompliant with medical therapy who presented with syncope, hematemesis, melena, and abdominal distension. The patient received intravenous levothyroxine with a good response and improved upon discharge. This case highlights the importance of considering hypothyroidism as an etiology of unexplained ascites. The analysis of ascites from myxedema may not always have a significantly elevated protein (>2.5g/dL). Appropriate diagnosis should also rely on the clinical presentation along with a rapid and positive response to thyroid hormone replacement therapy.